Return of the Underwear Dragon - Rothman, Scott; Oswald, Pete (New York Random House Studio, 2021)
After realizing that the Underwear Dragon misbehaves only because he cannot read, Sir Cole and his would-be assistant, Claire, are determined to help the fearsome beast.
Sequel to: Attack of the Underwear Dragon.
Ages 3-7.
Grades K-1.
111404
Keywords: Knights and knighthood -- Juvenile fiction; Literacy -- Juvenile fiction; Books and reading -- Juvenile fiction; Dragons -- Juvenile fiction; Apprentices -- Juvenile fiction; Humorous stories; Juvenile FIciton / Animals / Dragons, Unicorns & Mythical; Juvenile FIciton / Imagination & Play; Humorous stories; Humorous fiction; Juvenile works; Picture books